Direct space–time manipulation mechanism for spatio-temporal coupling of ultrafast light field - Qinggang Lin; Fu Feng; Yi Cai; Xiaowei Lu; Xuanke Zeng; Congying Wang; Shixiang Xu; Jingzhen Li; Xiaocong Yuan (Nature Communications, 2024)
Abstract Traditionally, manipulation of spatiotemporal coupling (STC) of the ultrafast light fields can be actualized in the space-spectrum domain with some 4-f pulse shapers, which suffers usually from some limitations, such as spectral/pixel resolution and information crosstalk associated with the 4-f pulse shapers. This work introduces a novel mechanism for direct space-time manipulation of ultrafast light fields to overcome the limitations. This mechanism combines a space-dependent time delay with some spatial geometrical transformations, which has been experimentally proved by generating a high-quality STC light field, called light spring (LS). The LS, owing a broad topological charge bandwidth of 11.5 and a tunable central topological charge from 2 to −11, can propagate with a stable spatiotemporal intensity structure from near to far fields. This achievement implies the mechanism provides an efficient way to generate complex STC light fields, such as LS with potential applications in information encryption, optical communication, and laser-plasma acceleration.